Czesław Miłosz’s and Gilbert Durand’s structures of the imaginary - Lubelska-Renouf, Magdalena (Prace Polonistyczne, 2023)
Gilbert Durand, the author of the classic The Anthropological Structures of the Imaginary, initiated a new area of research in the humanities, first in France and then worldwide. He proposed a morphological classification of broadly conceived structures of the imaginary, which includes symbols, images, and myths that are specific to a given author or culture. Drawing on various disciplines, Durand’s work can be seen as a vast undertaking aimed at rehabilitating the imaginary. He sees the imaginary is an art of human intellectual life and an essential aspect of human nature. Dreams, symbols, and images together constitute a kind of “transcendental fantastic”, without which a human being cannot experience wholeness or completeness. The article argues that the works of Czesław Miłosz, in which images form veritable magnetic fields gravitating around a number of central poetic symbols, can be read as a practical implementation of Durand’s theories. Artykuł Magdaleny Lubelskiej-Renouf Czesław Miłosz’s and Gilbert Durand’s Structures of the Imaginary w języku polskim dostępny w: „Prace Polonistyczne” 2019, seria LXXIV, s. 29–51 (Magdalena Lubelska-Renouf, Struktury wyobraźni Czesława Miłosza i Gilberta Duranda).